The Principal's Visionary Leadership Transforms Quality: Good Example and Habits - Kusumawati, Erna (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The importance of "example" and "good habits" as essential mechanisms for principals' visionary leadership in attaining "exceptional quality." This study investigates how principals can play a visionary leadership role in improving school quality through good examples and practices. This study aims to analyze leadership strategies, given the importance of leadership for improving educational quality. This study employed mixed methods, combining qualitative and quantitative methods. Subjects included principals, teachers, and students from five high-achieving schools, using a mixed approach consisting of interviews, observations, and qualitative and quantitative surveys. The results indicate that ethical principles and positive habits, such as wearing a practice uniform and reflecting on disruption, significantly increase pedagogical innovation and build a culture of quality. This study advances understanding of transformative leadership and has practical implications for improving the quality of science- and technology-based schools.